Dampak pembelajaran daring di masa pandemi terhadap pemahaman materi mahasiswa FKIP UNTIRTA - Pambudi, Gigih Adhi; Subhan Widiansyah (ARKA INSTITUTE, 2022)
Online learning is an alternative that can overcome the problem of disruption of the conventional learning process during the Covid-19 pandemic. In online learning there are many obstacles faced by students or even lecturers. In online learning, the problem that is often faced by students is network problems. A bad network connection will affect the message or explanation of the material conveyed by the lecturer. With the disruption of the network, students often find it difficult to understand the explanation conveyed by the lecturer, because the sound that is heard tends to be less clear. Therefore, this study aims to explain in detail the impact of online learning on the understanding of FKIP Untirta students during the Covid-19 Pandemic. By using a descriptive qualitative approach in the form of observation. With the subject of observations of FETT Untirta students. The discussion is focused on the impact that online learning has on students' understanding of the material. The results of this research show the effect of online learning on students' understanding of material, the problems faced by students and the obstacles in doing online learning. George Hebert Mead explained that social interaction can work if there is an exchange of symbols which later creates a meaning that can create an interaction, including online communication. Where in online communication there must also be an exchange of symbols which later the symbol also forms a meaning.